The association between psychotic-like experiences and violent behavior in adolescents: a cross-lagged longitudinal study - Zhou, Rui; Foo, Jerome Clifford; Nishida, Asuka; Ogawa, Sayoko; Togo, Fumiharu; Sasaki, Tsukasa (European child & adolescent psychiatry, 2025)
Psychotic-like experiences (PLEs) have been identified as risk factors for mental health issues and behavioral problems including violence. While cross-sectional studies suggest an association between PLEs and violent behavior in adolescents, their longitudinal relationship remains unexamined. This study aims to examine the temporal association between PLEs and violent behavior in adolescents. PLEs and violent behavior were assessed using data from self-report surveys conducted from 2011 to 2019 in a Tokyo junior and senior high school (grades 7-12). The study included 1685 participants aged 12-18 surveyed annually for up to 6 years. Random intercept cross-lagged panel models (RI-CLPMs) were used to examine between-person and within-person associations among study variables, with analyses stratified by gender. Results showed a bidirectional relationship between PLEs and violent behavior on both the between-person (β = 0.23, p < 0.001) and within-person levels (β = 0.07-0.25, p < 0.05). This relationship was significant for PLEs and violence towards objects (between-person: β = 0.22, p < 0.001; within-person: β = 0.07-0.32, p < 0.05), but not for PLEs and interpersonal violence. When analyzed by gender, these associations were significant in girls but not in boys. The findings suggested that PLEs may have a bidirectional relationship with violent behavior (especially violence towards objects), particularly in girls, indicating potential gender-specific pathways in this association. Further research should explore the underlying mechanisms of this bidirectional relationship, with a focus on gender-specific factors.